Preparation of Titanium Dioxide Nanoparticles and PolyVinyl Pyrrolidone Polymer Films as Antibacterial, Antibiofilm against Pathogenic Bacteria on Different Surfaces - Salman, Jehan Abdul Sattar; Hadi AL-Kadhemy, Mahasin F.; Madhloom, Samara A. (Malaysian Journal of Science, 2017)
In this paper, the structural properties that included X-ray diffraction (XRD) of Polyvinyl Pyrrolidone (PVP) and PVP with titanium dioxide nanoparticles have studied. PVP still appeared amorphous structure in spite of presence of titanium dioxide nanoparticle with crystalline form. The films of pure PVP and PVP with titanium dioxide nanoparticle have been prepared by casting method and used in covering glass plates and plastic to study the effect of these films on growth of bacteria. The antibacterial effect against Staphylococcus aureus and Escherichia coli has been tested. In this study the prepared films had antibacterial effect on plastic and glass plates, the reduction of bacterial growth percentage for PVP films on plastic and glass plates reached to 60.89% and 62.5% against S. aureus and 49%, 51% against E. coli, respectively. Whereas the percentage for prepared films from a mixture of PVP with titanium dioxide nanoparticle on plastic and glass plates reached 89.42% and 86%, respectively against S. aureus and 100% , 69% against E.coli. Antibiofilm effect of PVP with titanium dioxide nanoparticle against pathogenic bacteria on catheters was studied for (4) weeks. PVP with titanium dioxide nanoparticle films had the ability to inhibit biofilm formation for pathogenic bacteria on catheters, the inhibition of biofilm percentage reached to 83.97% against S.aureus and 65.3% against E.coli after fourth week of storage. Keywords: (PVP) Polymer; TiO2 nanoparticles; Antibacterial Activity; Antibiofilm; Staphylococcus aureus and Escherichia coli; catheters.